IMPROVE WORKER PERFORMANCE ON PT. PLN.(PERSERO) BALI DISTRIBUTION MAIN UNIT - I Nyoman Resa Adhika; I Gede Rihayana; Putu Pradiva Putra Salain (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
The performance of employees at PT PLN (Persero) Bali Distribution Parent Unit decreased allegedly because there are still employees who are not competent in their work, other causes are suspected to be due to work placements that are not in accordance with the latest educational background of the employee, and there are still some employees who do not have career development opportunities (transfers and promotions). This study aims to determine and analyze the effect of competence, job placement and career development on employee performance at PT PLN (Persero) Bali Distribution Parent Unit. The research population is 154 employees at the Main Office of PT PLN (Persero) Bali Distribution Main Unit. The sample in this study was 61 employees who were determined based on the simple random sampling method. The analytical tool used to test the hypothesis is multiple linear regression analysis. The results showed that competence had a positive and significant effect on employee performance at PT. PLN (Persero) Bali Distribution Parent Unit, work placement has a positive and significant effect on employee performance at PT. PLN (Persero) Bali Distribution Parent Unit, career development has a positive and significant effect on employee performance at PT. PLN (Persero) Main Unit Distribution Bali. Further research if you want to examine employee performance should take variables other than those used in this study.